Nilai Ekonomi Kawasan Hutan Mangrove Bagi Nelayan Sekitar Area Pertambangan PT. SILO Kotabaru, Kalimantan Selatan - Leila Ariyani Sofia; Erma Agusliani; Fitria Purnamasari (Universitas Lambung Mangkurat, 2021)
The mangrove forest area of PT. SILO (Sebuku Iron Lateric Ores) Kotabaru company has a mining concession area of ± 9,771 ha, around ± 85 ha of the areas are mangrove forest area that have been freed from mining activities. However, this company plans to manage this area to be an ecotourism forest in order to provide the economic value around the communities. This study aims to investigate the economic value of mangrove forest areas based on three criterions of benefit: (1) direct, indirect, and optional benefit. The primary data were collected using several method: survey, observation, and interviews with fishermen and communities around the area. A total of 22 respondents of 150 fishermen were interviewed randomly: 15 fish/shrimp fishermen, 2 clam catchers, 4 mud crab catchers, and 1 mud crab cultivator. The collected data were analyzed descriptively and total economic valuation analysis using quantification technique of market prices, indirect prices, and replacement values. The results showed the economic value of the mangrove forest area for direct benefit was IDR 10,082,232,500 year-1 (shrimp IDR 9,411,573,000; fish IDR 265,717,000; clam IDR 99,242,500; and mud crabs Rp. 305,700,000. The indirect benefit was Rp. 10,578,857,143 year-1 and as an abrasion barrier was 174,082,920 year-1 , while the value of the selected benefits was Rp. 17,901,000 year-1 . In conclusion, the value of strategic developed areas is literally integrated mangrove aquaculture (silvofishery) and mangrove ecotourism.